2012
DOI: 10.1097/hjh.0b013e32834dde5f
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan ameliorates lipopolysaccharide-induced innate immune response through peroxisome proliferator-activated receptor-γ activation in human monocytes

Abstract: Objective Angiotensin II type 1 receptor (AT1) blockers (ARBs) reduce the bacterial endotoxin lipopolysaccharide (LPS)-induced innate immune response in human circulating monocytes expressing few AT1. To clarify the mechanisms of anti-inflammatory effects of ARBs with different peroxisome proliferator-activated receptor-γ (PPARγ)-activating potencies, we focused our study on telmisartan, an ARB with the highest PPARγ-stimulating activity. Methods Human circulating monocytes and monocytic THP-1 (human acute m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…Thus, telmisartan prevented hydronephrosis development after unilateral ureteral obstruction in AT1R knockout mouse, an effect that was partly mimicked by losartan and blocked by GW9662 (Kusunoki et al, 2012). The telmisartaninduced expression of ATP binding cassette transporters A1 and G1 and of the scavenger receptor class B type 1 in THP-1 was abolished by PPAR-g siRNA in murine (Nakaya et al, 2007;Matsumura et al, 2011) and human macrophages (Pang et al, 2012). siRNA-induced PPAR-g knockdown abolished the ability of telmisartan to delay endothelial senescence during repeated passaging (Scalera et al, 2008).…”
Section: A Peroxisome Proliferator-activated Receptorsmentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, telmisartan prevented hydronephrosis development after unilateral ureteral obstruction in AT1R knockout mouse, an effect that was partly mimicked by losartan and blocked by GW9662 (Kusunoki et al, 2012). The telmisartaninduced expression of ATP binding cassette transporters A1 and G1 and of the scavenger receptor class B type 1 in THP-1 was abolished by PPAR-g siRNA in murine (Nakaya et al, 2007;Matsumura et al, 2011) and human macrophages (Pang et al, 2012). siRNA-induced PPAR-g knockdown abolished the ability of telmisartan to delay endothelial senescence during repeated passaging (Scalera et al, 2008).…”
Section: A Peroxisome Proliferator-activated Receptorsmentioning
confidence: 92%
“…In murine macrophages telmisartan but not losartan, olmesartan, or valsartan activated PPAR-g (Matsumura et al, 2011). PPAR-g activation by telmisartan was also shown in human macrophages (Pang et al, 2012). Site-directed mutagenesis studies using reporter gene readouts have indicated that the binding of telmisartan to PPAR-g has distinct structural requirements compared with that of the thiazolidinediones (Tagami et al, 2009).…”
Section: A Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…7) Thus, apart from being a major vasopressor effector of the renin-angiotensin system, ARBs are probably good candidate drugs for inflammation.…”
Section: )mentioning
confidence: 99%
“…Flavonoids are also recognized moiety for antifungal, cytotoxic, neuroprotective and HIVinhibitory antimicrobial and antifungal properties [6][7][8][9][10][11][12][13] . The synthesis, spectral study and biological activity significance for flavone molecule 6-chloro-2-(furan-2-yl)-4-oxo-4H-chromen-3-yl acetate was reported [14][15][16] . In this work, we report the crystallographic studies to have more insight view of molecular structure and physical property of title compound.…”
Section: Introductionmentioning
confidence: 99%